Mission San Luis de Tolosa, Founded 1772, San Luis Obispo, California [front and back] (1908)
Back of postcard has writing indicating the postcard was sent from 1029 O St. Fresno, California, and addressed to Mrs. H. Victors, San Jos?, California. Note in bottom left hand corner reads: Hawthorn Farm R.D. No.1.